Effect of Blood Pressure Lowering in Early Ischemic Stroke: Meta-Analysis. Issue 7 (July 2015) - Lee, Meng; Ovbiagele, Bruce; Hong, Keun-Sik; Wu, Yi-Ling; Lee, Jing-Er; Rao, Neal M.; Feng, Wayne; Saver, Jeffrey L.
Abstract : Background and Purpose—: Elevated blood pressure is common in acute stage of ischemic stroke and the strategy to manage this situation is not well established. We therefore conducted a meta-analysis of randomized controlled trials comparing active blood pressure lowering and control groups in early ischemic stroke. Methods—: Pubmed, EMBASE, and Clinicaltrials.gov from January 1966 to March 2015 were searched to identify relevant studies. We included randomized controlled trials with blood pressure lowering started versus control within 3 days of ischemic stroke onset. The primary outcome was unfavorable outcome at 3 months or at trial end point, defined as dependency or death, and the key secondary outcome was recurrent vascular events. Pooled relative risks and 95% confidence intervals were calculated using random-effects model. Results—: The systematic search identified 13 randomized controlled trials with 12 703 participants comparing early blood pressure lowering and control. Pooling the results with the random-effects model showed that blood pressure lowering in early ischemic stroke did not affect the risk of death or dependency at 3 months or at trial end point (relative risk, 1.04; 95% confidence interval, 0.96–1.13; P =0.35). Also, blood pressure lowering also had neutral effect on recurrent vascular events, as well as on disability or death, all-cause mortality, recurrent stroke, and serious adverse events. Conclusions—: This meta-analysis suggested blood pressure lowering in early ischemic stroke had a neutral effect on the prevention of death or dependency.